Identification of a new recombinant strain of echovirus 33 from children with hand, foot, and mouth disease complicated by meningitis in Yunnan, China - Zhang, Jie (Virol J, 2019)
BACKGROUND: Hand, foot, and mouth disease (HFMD) is a common childhood disease, which is usually caused by enterovirus A (EV-A) serotypes. Enterovirus A71 (EV-A71) and coxsackievirus A16 (CV-A16) are the main etiologic agents. Multiple serotypes of enterovirus B serotypes (EV-B) have been detected in outbreaks or sporadic cases of HFMD. RESULTS: During HFMD surveillance in Yunnan, China in 2013, two echovirus 33 (E-33) isolates were recovered in cell culture and typed by molecular methods from the cerebrospinal fluid (CSF) and feces of two sporadic cases of HFMD complicated by meningitis. Sequence analysis indicated that the study isolates, YNK35 and YNA12, formed an independent branch, and belonged to E-33 genotype H. Recombination analysis indicated multiple recombination events in the genomic sequence of isolate YNK35. The recombination mainly occurred in the non-structural coding region of P2 and P3, and involved intra-species recombination of species B. CONCLUSION: In this study, the complete sequences of two E-33 isolates were determined. This is the first report of severe HFMD associated with E-33 in Yunnan China, and it enriches the number of full-length genome sequences of E-33 in the GenBank database. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12985-019-1164-2) contains supplementary material, which is available to authorized users.